PUBLIC SPENDING EFFICIENCY AND POLITICAL AND ECONOMIC FACTORS: EVIDENCE FROM SELECTED EAST ASIAN COUNTRIES - Chan Mohd, Sok-Gee; Abd Karim, Zaini (Economic Annals, 2012)
This paper analyses public spending efficiency and the effect of political and economic factors on public spending efficiency in East Asian countries for the period 2000-2007. In the first stage, the non-parametric Data Envelopment Analysis (DEA) approach is used to estimate public spending efficiency scores. In the second stage, the Tobit regression model is then used to determine the effect of political and economic factors on public spending efficiency. Results of the study show that China is relatively efficient in public spending on education, health, and maintaining economic performance and stability, Japan on infrastructure, and Singapore on promoting public services. In addition, countries in East Asia are relatively less efficient in public spending for promoting equal income distribution. The results also indicate that political stability and financial freedom have a positive effect on public spending efficiency. However, voice, accountability, and civil liberties have a negative effect on public spending efficiency.